2018
DOI: 10.1016/j.str.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the G119S Mutant Acetylcholinesterase of the Malaria Vector Anopheles gambiae Reveals Basis of Insecticide Resistance

Abstract: Malaria is a devastating disease in sub-Saharan Africa and is transmitted by the mosquito Anopheles gambiae. While indoor residual spraying of anticholinesterase insecticides has been useful in controlling the spread of malaria, widespread application of these compounds has led to the rise of an insecticide-resistant mosquito strain that harbors a G119S mutation in the nervous system target enzyme acetylcholinesterase. We demonstrate the atomic basis of insecticide resistance through structure determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 56 publications
3
57
0
Order By: Relevance
“…Their overall structures are, nevertheless, very similar (1.9 Å rmsd) [8]. The structure of AgAChE notably confirmed the existence of an open channel at the base of the active-site gorge [9], as previously identified in DmAChE [6]. It is suggested that this particular structural feature could be exploited to design highly specific insecticides.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Their overall structures are, nevertheless, very similar (1.9 Å rmsd) [8]. The structure of AgAChE notably confirmed the existence of an open channel at the base of the active-site gorge [9], as previously identified in DmAChE [6]. It is suggested that this particular structural feature could be exploited to design highly specific insecticides.…”
Section: Introductionsupporting
confidence: 74%
“…These structures provided the first rational basis for explaining differences in specificity and activity between DmAChE and mammalian AChEs. Recently, crystal structures of another insect AChE have been published, that of the wild type Anopheles gambiae AChE (AgAChE) [8] and of an insecticide-resistant mutant of the same enzyme [9]. The sequence similarity of AgAChE and DmAChE is relatively low (41.1% identity) since they are coded by non-homologous genes, ace-1 and ace-2, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in culicine and anopheline mosquitoes have found that non-synonymous mutations in Ace1 can result in resistance to carbamates and organophosphates other than pirimiphos-methyl (Weill et al 2003(Weill et al , 2004Feyereisen et al 2015). The most common mutation in Anopheles is a glycine to serine mutation in codon 280 (G280S, also known as G119S after the codon numbering of a partial crystal structure from the electric ray Torpedo californica (Weill et al 2003;Greenblatt et al 2004;Feyereisen et al 2015)), which is located near the active site gorge of ACE1 (Cheung et al 2018) and decreases its sensitivity to organophosphates and carbamates.…”
Section: Introductionmentioning
confidence: 99%
“…The most salient of these additional mutations was a serine-to-alanine SNP in codon 65 (S65A), with frequencies of 30-50% in multiple West African populations. Codon 65 maps to the anopheline-specific N-terminal insertion of ACE1 proteins (Supplementary Material SM1), which lacks predicted secondary structure and is far away from the active-site gorge of the enzyme (Cheung et al 2018). This position is not conserved across ACE1 orthologs, being variously encoded as alanine, serine or threonine in different Anopheles species (Supplementary Material SM1).…”
Section: Introductionmentioning
confidence: 99%